1990
DOI: 10.1099/0022-1317-71-12-2773
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Plum Pox Potyvirus Polyprotein Processing By the NIa Protease in Escherichia Coli

Abstract: A binary Escherichia coli expression system has been used to study the pathway for proteolytic processing of the plum pox potyvirus (PPV) polyprotein. Trans cleavage at the carboxyl end of the cylindrical inclusion protein occurred, although with lower efficiency than that at the large nuclear inclusion protein-capsid protein junction. No trans cleavage at the carboxyl end of the small nuclear inclusion protein (NIa) was detected. The proteolytic activities at different cleavage sites of several deletion and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The results obtained suggest that the recognition and catalytic sites of the NIa proteases are closely interlinked and that the main determinants for substrate specificity lie in the Cterminal one-third of the protease . It has also been suggested that the extreme carboxyl end of the protease could be involved in maintenance of the proper structure that would allow other parts of the protein to interact correctly with the various cleavage sites, since the effect caused by different mutations in this region depends on the cleavage site considered (Carrington & Dougherty, 1987a;Garcia et al, 1990). Finally, it has been shown that the potyviral NIa protease processes a great deal of substrate efficiently (Garcia et al, 1989c).…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained suggest that the recognition and catalytic sites of the NIa proteases are closely interlinked and that the main determinants for substrate specificity lie in the Cterminal one-third of the protease . It has also been suggested that the extreme carboxyl end of the protease could be involved in maintenance of the proper structure that would allow other parts of the protein to interact correctly with the various cleavage sites, since the effect caused by different mutations in this region depends on the cleavage site considered (Carrington & Dougherty, 1987a;Garcia et al, 1990). Finally, it has been shown that the potyviral NIa protease processes a great deal of substrate efficiently (Garcia et al, 1989c).…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 99%
“…NIa protease is catalytically active within the polyprotein, excising itself by cis cleavages at sites D and E in a process that might happen as a primary event (maybe cotranslational) in the proteolytic cascade (Carrington & Dougherty, 1987a, b;Hellmann et al, 1988;Garcia et al, 1990). In summary, NIa-catalysed proteolytic maturation of the potyviral polyprotein is a regulated process involving cis and trans cleavages at sites which are recognized with different efficiencies and processed at different rates.…”
Section: Genome Expression: Polyprotein Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was terminated after 30 min by addition of 6 times loading dye and was monitored by electrophoresis on 0.7% agarose gel followed by ethidium bromide staining. Lanes 3,5,7,9, and 11 represent the reaction products of His-tagged NIa, NIa C151A, NIa H46A, NIa D81N, and NIa D81G proteinase, respectively; lanes 4,6,8,10, and 12 represent the reaction products of GST-fused NIa, NIa C151A, NIa H46A, NIa D81N, and NIa D81G proteinase, respectively; samples with heat-denatured His-tagged NIa and GST-NIa added as negative control are represented in lanes 1 and 2, respectively. B, phage DNA (50 g) was incubated with purified His-tagged NIa proteinase (5 g) in 20 mM Tris-HCl, pH 8.2, containing 1 mM MgCl 2 at 37°C for different times, and the reaction was stopped by addition of equal volumes of acid lanthanum reagent (20 mM La(NO 3 ) 3 in 0.2 N HCl). The precipitate was removed by centrifugation, and absorbance of the supernatant solution was measured at 260 nm against a blank sample without enzyme.…”
Section: Fig 2 Proteinase Activity Of Recombinant Pvbv Nia and Its mentioning
confidence: 99%
“…Site-specific mutagenesis studies with tobacco etch virus (TEV) (13), Plum pox potyvirus (8), and PVBV NIa proteinases (9) have unequivocally established the role of His-Asp-Cys in forming the catalytic triad responsible for the cleavage by the proteinase. The specificity of these proteinases is determined by the heptapeptide recognition sequence surrounding each cleavage site (10,11).…”
mentioning
confidence: 99%